2022
DOI: 10.32604/iasc.2022.021206
|View full text |Cite
|
Sign up to set email alerts
|

Optimized U-Net Segmentation and Hybrid Res-Net for Brain Tumor MRI Images Classification

Abstract: A brain tumor is a portion of uneven cells, need to be detected earlier for treatment. Magnetic Resonance Imaging (MRI) is a routinely utilized procedure to take brain tumor images. Manual segmentation of tumor is a crucial task and laborious. There is a need for an automated system for segmentation and classification for tumor surgery and medical treatments. This work suggests an efficient brain tumor segmentation and classification based on deep learning techniques. Initially, Squirrel search optimized bidir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The authors demonstrated that the proposed algorithm achieved good precision compared to similar algorithms and improved the classification of training pixels and lesion localization accuracy. Finally, in this paper ( Rajaragavi & Rajan, 2022 ), the authors proposed a new hybrid model called “ConvLSTM-UNet” for the automatic detection of pneumonia from chest X-ray images. The authors demonstrated that the proposed model outperformed several state-of-the-art models for pneumonia detection in terms of accuracy, sensitivity, specificity, and AUC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors demonstrated that the proposed algorithm achieved good precision compared to similar algorithms and improved the classification of training pixels and lesion localization accuracy. Finally, in this paper ( Rajaragavi & Rajan, 2022 ), the authors proposed a new hybrid model called “ConvLSTM-UNet” for the automatic detection of pneumonia from chest X-ray images. The authors demonstrated that the proposed model outperformed several state-of-the-art models for pneumonia detection in terms of accuracy, sensitivity, specificity, and AUC.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Then, the feature F t e−256 is fed into the GPG module to restrain the local segmentation errors of low-level feature space. Besides, we aggregate the information progressively from the top level to the low level like the U-Net architecture [26] through a simple feature fusion operation. At last, as mentioned in Section 4, an MEI module is used to refine the coarse segmentation results.…”
Section: Overview Of Global Position Guidance and Multi-path Explicit...mentioning
confidence: 99%
“…ResNet is known for its residual connections and achieves high accuracy in tasks such as brain tumor segmentation [ 18 ]. U-Net precise localization has been extensively applied to segment brain MR images [ 19 ]. Many researchers have combined ResNet and U-Net to leverage their respective strengths for enhanced accuracy and precision [ 20 ].…”
Section: Introductionmentioning
confidence: 99%